Effects of enclosure measures on soil water infiltration and evaporation in arid and semi-arid grassland in northern China - Fan, Cairui; Guo, Jinyan; Li, Xiu; Zhang, Chengfu; Wang, Teng (Frontiers in Environmental Science, 2024)
Soil infiltration and evaporation are major factors affecting the water cycle in arid and semi-arid areas. In order to explore the impact of different enclosure years on soil water infiltration and evaporation in the Hulun Buir grassland, taking the enclosure time of Hulunbuir grassland for 3 years, 7 years, 10 years and the grazing control grassland as the research objects by using small evaporation instrument and double-ring infiltration instrument.To study the effects of enclosure measures on soil water distribution, soil infiltration and evaporation, and to evaluate the applicability of the main soil evaporation and infiltration models in enclosed grassland. The results show that the enclosure measures can effectively improve the soil water content. In the vertical direction, the soil water content shows a trend of increasing first and then decreasing. The initial infiltration rate and stable infiltration rate of grassland at different enclosure time are significantly different (P<0.05), and the soil infiltration rate and evaporation rate were in the order of EN10 >EN7 >EN3 >CK. Using three infiltration process models to simulate the grassland infiltration process at different enclosure times, the Horton model is able to better model the inflection points of the infiltration process, and the fit accuracy is higher than that of the Philip and Kostiakov models. The cumulative evaporation process of grassland at different closure times was simulated by using Black, Ross, and Power function models.The simulation values calculated by the Rose model are the closest to the measured value, and the simulation accuracy is the highest.The comprehensive analysis shows that the hydrological characteristics of grassland soil change significantly in the early stage of enclosure phase, and the soil properties have reached a good state for 3 to 7 years.With the continuous increase of enclosure time, the change of soil hydrological characteristics is not obvious.